Self-assessed bankruptcy probability among civil servants in Putrajaya, Malaysia - Yasotha Nair, Tramankuti (2016)
Nowadays, many people are having trouble in stretching out their finances in a growing national economy and gaining in real household income. Mismanagement of financial resources add up to the number of bankruptcy incidents among civil servants in the country. The extent to which poor financial management has contributed to this problem is not empirically assured. Understanding the determining factors related to the bankruptcy among civil servants is crucial to develop appropriate strategies in the government system to promote a better financial standing among civil servants.This study was primarily aimed to examine the factors predicting self-assessed bankruptcy probability among civil servants in Putrajaya, Malaysia objectively and subjectively. It was also sets out to determine the relationship between self-assessed bankruptcy probability and the level of economic concern on future finance, attitude towards debt and asset ownership which is mediated by financial management practices. The Theory of Reasoned Action (TRA), Theory of Conspicuous Consumption and Family Systems Management Model were used to predict selfassessed bankruptcy probability.Samples of 399 Malaysian civil servants from Putrajaya were selected through multistage cluster sampling. Data for the research was collected through an electronic survey at five ministries in Putrajaya. They were segregated according to their occupational grade (Management & Professional and Supportive Group). Research instruments had verified adequate levels of internal consistency, reliability, and content validity according to the past researches. The research estimated model was tested by using descriptive analysis, chi square test, independent t-test, binary logistic egression,financial ratios and mediation analysis. Specifically, the mediation approach of Preacher and Hayes (2004; 2008) using bootstrapping was employed to measure the mediating effect of financial management practices between economic concern on future finance, attitude towards debt and self-assessed bankruptcy probability.Results of the study revealed that economic concern on future finance, attitude towards debt, asset ownership and financial management practices had a significant effect on self-assessed bankruptcy probability. To illustrate, Putrajaya civil servants had a positive concern on their future finance. Besides that, 87 percent of the civil servants positively had rational attitude towards debt. Subsequently, they also practiced a good level of financial management especially in relation to credit management, cash management, credit planning and general management with the exception for risk management.Moreover, the role of financial management practices mediating the relationship between the level of attitude towards debt and economic concern on future finance as well as self-assessed bankruptcy probability were also highlighted and discussed.Results also indicated the major predictors that influenced self-assessed bankruptcy probability were age, gender, marital status, number of children, occupational grade,economic concern on future finance, attitude toward debts, financial management practices, asset ownership and liquidity ratio. Apart from that, the findings of financial ratio in this study were considered fairly stable considering 95 percent of the civil servants achieved the minimum requirement by fulfilling only one to three financial ratios. It was also shown that five percent of the civil servants were identified to have self-assessed bankruptcy probability.The study contributed to the body of knowledge by providing empirical evidence and improved the understanding of self-assessed bankruptcy probability. Consequently,the findings of this study may be used as a basis to improve financial management practices, hence preventing and reducing financial problems and self-assessed bankruptcy among civil servants in Putrajaya, Malaysia.